Deep Lateral Wall Partial Rim-Sparing Orbital Decompression with Ultrasonic Bone Removal for Treatment of Thyroid-Related Orbitopathy - Álvaro Bengoa-González; Alicia Galindo-Ferreiro; Enrique Mencía-Gutiérrez; Hortensia Sánchez-Tocino; Agustín Martín-Clavijo; María-Dolores Lago-Llinás (Journal of Ophthalmology)
Purpose. To describe the results of thyroid-related orbitopathy (TRO) treated by ultrasonic deep lateral wall bony decompression with partial rim sparing (DLW-PRS). Methods. A review was carried out, from January 2015 to September 2017, of all patients treated with ultrasonic DLW-PRS decompression using a SONOPET® (Stryker, Kalamazoo, MI, USA) ultrasonic aspirator, using a lateral, small triangle flap incision for access. The primary outcome was the change in proptosis (measured by the difference in Hertel exophthalmometry measurements). Other secondary outcomes were changes in visual acuity (VA) (using Snellen scale, decimal fraction), presence of lagophthalmos, eyelid retraction (measured by upper eyelid margin distance to the corneal reflex (MRD1) and lower eyelid margin distance to the corneal reflex (MRD2), and presence of exposure keratopathy). Results. A total of 58 orbital decompressions in 35 patients were reviewed, with 23 patients (65.7%) having bilateral decompressions. There was a female preponderance with 26 patients (74.2%), and the mean age ± standard deviation was 52.6 ± 13.9 years. Mean proptosis was 24.51 ± 1.76 mm preoperatively, reduced to 19.61 ± 1.27 mm in final follow-up. The mean reduction was 4.9 ± 1.54 mm. VA improved from 0.8 ± 0.14 to 0.9 ± 0.12, p=0.039. 5 of 13 patients (38.4%) with preoperative diplopia reported improvement or complete resolution after surgery. MRD1 was reduced from 5.25 ± 0.88 mm to 4.49 ± 0.7 mm. MRD2 was also reduced from 6.3 ± 0.88 mm to 5.0 ± 0.17 mm. Presence of lagophthalmos was reduced from 35 eyes (60.3%) to five (8.6%); the presence of epiphora was also reduced from 20 patients (57.1%) to 3 (8.5%) following decompression. Complications of the surgery included zygomatic hypoaesthesia in 14 (40%) patients in the early postoperative period and chewing alterations in 10 (28.5%) of the patients. All of these complications were resolved at the 6-month follow-up visit. We noted no surgical complications such as ocular or soft tissue damage, infection, inflammation, or visual loss. Conclusions. The SONOPET® ultrasonic bone curette can be used safely and effectively for DLW orbital decompression surgery. The main benefits were good visualization and handling of tissues and speed and ease of use of the equipment. This trial is registered with ClinicalTrials.gov identifier: NCT04025034.